Pengaruh Keselamatan Tempat Kerja dan Budaya Aman terhadap Retensi Karyawan dan Loyalitas Karyawan - Khoirur Rozaq (LITERATUS, 2022)
This study examines and analyzes the influence of workplace security and safety culture on employee retention and loyalty. The population in this study were all employees working at manufacturing companies in Gresik. Sampling using a simple random sampling technique, and the sample used in this study was 60 samples. This research aims to understand entrepreneurs, especially those engaged in manufacturing because the worker safety factor is significant. Employers can retain the best employees and increase employee loyalty to the organization. Methods This research takes a quantitative approach by using a cross-sectional design. Research sources come from primary sources obtained through questionnaires and secondary sources from articles related to the research topic. Research data collection through questionnaires using a five Likert scale with five alternative answers—analysis of research data using multiple linear regression tests that had previously been through the classical assumption test using SPSS version 24. The test results show that all the hypotheses proposed have a significant effect. Employee loyalty, workplace security, and safety culture significantly impact retention and work safety and security culture positively affect employee loyalty. The implication for practitioners based on this research is that workplace safety is a basic need for employees that employers must meet. Organizations must also implement a good workplace safety culture to increase loyalty and retain employees.